Analisis Perlakuan Akuntansi Psak No. 10 Atas Selisih Kurs dan Transaksi Mata Uang Asing pada PT Kalbe Farma Tahun 2022 - Yumna Qoni’atun Sholihah; Aleesya Mae Danieela; Azhilatul Annisa Parasti; Azkira Taradiva Fadya Putri; Erviana Agustina; Wulandari Agustiningsih (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research analyzes the management of foreign currency transactions and the impact of exchange rate differences on the financial statements of PT Kalbe Farma, a leading pharmaceutical company in Indonesia. Using a qualitative approach with literature study methods and secondary data analysis, this research focuses on the healthcare sector, which is understudied in the context of exchange rate fluctuation risk management. The results show that PT Kalbe Farma has implemented accounting treatments in accordance with PSAK No. 10 for foreign currency transactions. Exchange rate differences are recognized in the income statement, significantly impacting the company’s financial position. Although the company has planned risk management strategies such as foreign currency purchases and intensive monitoring, it has not implemented a formal hedging policy. These findings are expected to provide valuable insights for PT Kalbe Farma in optimizing financial management amidst global foreign exchange market volatility.